Penguatan Peran Bank Sampah dalam Mewujudkan Lingkungan Bersih dan Bernilai Ekonomis - Muh. Tafsir; Yana Fajrih; Eva Marin Sambo; A. Dahrul; Bungatang Tahir; Yudi Ahmad Sadeli; Dharmawaty Djharuddin (Lembaga Pengembangan Kinerja Dosen, 2026)
Urban waste management remains a major challenge in achieving a clean and sustainable environment, including in Bontoduri Sub-district, Makassar City. Waste banks, as a community-based waste management model, have significant potential to reduce waste generation while creating economic value. However, in practice, the role of waste banks has not been fully optimized due to limitations in institutional capacity, community participation, and managerial practices. This community service activity aimed to strengthen the role of waste banks in promoting a clean and economically valuable environment through participatory and community empowerment approaches. The methods employed included preparation, environmental education and socialization, waste bank management training, institutional mentoring, and activity evaluation. The program involved approximately 30 participants consisting of waste bank managers, local government representatives, and community members. The results indicated an increase in community awareness and understanding of waste segregation, improved managerial and administrative capacities of waste bank operators, and enhanced community participation in waste-saving activities. In addition, waste banks contributed to generating added economic value from household waste and reducing the volume of waste disposed of into the environment and landfills. This activity concludes that strengthening the role of waste banks through education, training, and continuous mentoring can serve as an effective strategy to support sustainable urban waste management based on circular economy principles.